Intertextuality, Plausibility, and Interpretation - Pelling, Christopher (Histos, 2013)
Are there differences in principle between intertextuality in historiography and in other genres? This paper explores that question with detailed analysis of three cases: Herodotus’ account of Marathon, Xenophon’s of the seizure of the Cadmeia, and Plutarch’s of the final days of Julius Caesar. Particular attention is paid to the value of intertextuality for interpretation, as echoes of classic models prompt reflection both on historical continuities and on changes. Any generic differences may be in terms of the different ways in which readers may care about real-life experiences and those in fiction; it may also be that interpretations of other genres may apply, in a filtered way, the same reading techniques that historiography encourages for its real-life narratives.